Nurturing Linguistic Abilities: Meeting the Needs of Linguistically Challenged Pupils in Cameroon - Bechem, Enow Parris Cecilia (An Overview of Literature, Language and Education Research Vol. 2, 2024)
This study outlines clear trajectories on the challenges, progress and future directions in this field of deaf education, elucidating potential avenues for innovation and enhancement in addressing the diverse needs of deaf pupils. The study applied Reigeluth’s Instructional Design Theory (1999). The theory holds that instruction can be broken down into more detailed components. When lessons are broken down into smaller steps and teachers make use of concrete materials, deaf pupils benefit from the lessons. There is a dire need for a true culture of collaboration between the teacher of the deaf and the regular teacher. The exact need for collaboration is influenced by the culture of the instruction and can be impossible when collaboration is not valued or actively pursued. Successful advocacy efforts require collaboration among parents, educators, community organizations, and policymakers to amplify the voices of deaf pupils and champion their needs.